Comparative effects of directive and non-directive counseling on self-concepts of truants - Cruz, Leonor R. 1952-
Much attention has been put on the different counseling techniques that would best assist an individual in achieveing sound decision-making and self-understanding. This study was conducted to find out whether counseling would have an effect in improving the self-concept of truants in Mariano Ponce High School. It made use of the pre-test and posttest experimental design. The researcher concluded that counseling, either done in the directive or non-directive process, has a positive effect on the self-concept of truants in Mariano Ponce High School.